A prospective randomized open label comparative study of efficacy and safety of intralesional measles, mumps, rubella vaccine versus 100% trichloroacetic acid application in the treatment of common warts - Saini, Saveta; Dogra, Naina; Dogra, Devraj (International Journal of Research in Medical Sciences, 2016)
Background:Treatment of warts represents a continuing challenge for dermatologists as many of the available therapeutic modalities are associated with unsatisfactory results and high recurrence rates. Several clinical trials have proved the efficacy of intralesional immunotherapy by different antigens including MMR vaccine in the treatment of different types of warts. Methods:Total 150 patients having common warts over hands and feet including palmar and plantar warts were included in the study and were randomly divided into two groups. Group 1 consisted of 87 patients in whom MMR vaccine was given intralesionally in the largest wart whereas in Group 2, 63 patients were applied 100% trichloroacetic acid locally to the warts. These treatments were repeated 2 weekly for total three treatments. Patients were assessed for treatment response monthly for 3 months. Results: A highly significant difference was found in the response rates between the two groups (p<0.001). In the MMR group, 49.43% patients had >75% improvement and 26.44% patients had complete resolution whereas in TCA group, 11.11 % had >75% improvement and 7.94% patients had complete resolution. In the MMR group, side effects included pain at the injection site 100%, flu like symptoms 1.15 %, post-inflammatory hyperpigmentation 1.15% and tenderness 1.15% whereas in the TCA group all patients experienced burning sensation and 2 (3.17%) patients had post-inflammatory hyperpigmentation. Conclusion: Intralesional MMR vaccine is an effective treatment for warts without any significant side effects.